Development of a User-Personalized Decision Support System for Contraception Method Selection - Karami, Ahmad Fahmi; Ekawati, Rany; Marier, Syauqi Muhammad; Susantini, Purwanti (Applied Information System and Management (AISM), 2025)
The number of unmet needs for contraception has not reached the target set by the Indonesian government, while the uneven distribution of health workers, the main source of information for contraception, is still an unresolved problem. The Internet serves as an alternative source of information for contraception selection. However, without personalization, it may lead to inappropriate choices. This study discussed the development of an information system for selecting contraceptives, incorporating a decision support system (DSS), enabling personalized recommendations based on user preferences to assist in determining the appropriate contraceptive method. The functionality of the information system was evaluated using black-box testing, conducted by reproductive health experts, while its usability was assessed based on ISO-9241-11:2018 standards with 25 respondents. The functional evaluation of the system showed that 14 functions successfully passed the testing procedures, while 2 functions failed. The usability evaluation yielded excellent results, with an overall score of 4.52. Based on these findings, the developed information system can serve as a medium for reducing the number of unmet needs for contraception by providing users with contraceptive information tailored to their preferences. Further research needs to enhance system information by integrating user medical reports and user location and evaluating the recommendation-to-selection conversion rate— the extent to which users follow the system’s recommendations when choosing contraceptives.